Māori and Pasifika language, identity, and wellbeing in Aotearoa New Zealand. (3rd July 2021) - Matika, Correna M.; Manuela, Sam; Houkamau, Carla A.; Sibley, Chris G.
ABSTRACT: For Māori and Pasifika living in Aotearoa New Zealand, language, identity, and wellbeing are inter-linked and multifaceted. However, as English is the most widely spoken language in Aotearoa New Zealand, some Māori and Pasifika peoples will not be able to speak their community language. Ratings of ethnic identity centrality, self-esteem, life satisfaction and the Personal Wellbeing Index of monolingual (English only) and bilingual Māori ( N  = 4691) and Pasifika peoples ( N  = 868) were compared using New Zealand Attitudes and Values Study data collected during 2018/2019. Bilingual Māori and Pasifika peoples reported higher levels of ethnic identity centrality than English only speaking Māori and Pasifika. Bilingualism also moderated the relationship between ethnic identity centrality and self-esteem. Pasifika who only speak English have relatively positive and similar levels of wellbeing to Pasifika who are bilingual whereas bilingualism seems to strengthen the relationship between ethnic identity and wellbeing for Māori.